Preprocedural anemia in females undergoing transcatheter aortic valve implantation: Insights from the WIN‐TAVI registry. Issue 5 (1st October 2020) - Nicolas, Johny; Claessen, Bimmer E.; Cao, Davide; Sartori, Samantha; Baber, Usman; Power, David; Chiarito, Mauro; Goel, Ridhima; Roumeliotis, Anastasios; Chandiramani, Rishi; Chen, Siyan; Chandrasekhar, Jaya; et al.
Abstract: Objectives: To assess the impact of anemia on clinical outcomes in female patients enrolled in the Women's InterNational transcatheter aortic valve implantation (WIN‐TAVI) registry. Background: Anemia is highly prevalent among females who constitute half of TAVI candidates, yet, its clinical significance remains poorly investigated. Methods: Patients were divided into three groups according to preprocedural hemoglobin (Hb) level: (1) no anemia (Hb ≥12 g/dl), (2) mild‐to‐moderate anemia (10 ≤ Hb <12 g/dl), and (3) severe anemia (Hb <10 g/dl). The primary outcome was the occurrence of Valve Academic Research Consortium (VARC)‐2 efficacy endpoint, a composite of mortality, stroke, myocardial infarction (MI), hospitalization for valve‐related symptoms or heart failure or valve‐related dysfunction at 1‐year follow‐up. Results: Hemoglobin level was available in 877 (86.1%) patients: 412 (47.0%) had no anemia, 363 (41.4%) had mild‐to‐moderate anemia, and 102 (11.6%) had severe anemia. The latter group had a higher prevalence of cardiovascular risk factors. Compared with patients without anemia, severe anemia was associated with a greater risk of VARC‐2 efficacy endpoint (adj HR 1.71, 95% CI: 1.02–2.87, p = .04), all‐cause death (adj HR 2.36, 95% CI: 1.31–4.26, p = .004) and a composite of death, MI or stroke (adj HR 1.88, 95% CI: 1.10–3.22, p = .02) at 1 year. Moreover, an increased risk of late mortality (adj HR 1.15, 95% CI: 1.02–1.30, p = .03) was observed with every 1 g/dl decrease in hemoglobin level. Conclusion: Severe anemia in females undergoing TAVI was independently associated with increased rates of VARC‐2 efficacy endpoint and mortality at 1 year.